Peningkatan Pemahaman Perhitungan PPh Pasal 21 Pada Siswa SMK Ibnu Taimiyah Pekanbaru - Ika Wulandari; Leni Rahmayana; Mohd.Ideal Kurniawan; Nurhanimah (Pusat Riset dan Inovasi Nasional, 2022)
Community service activities carried out by the Pekanbaru LP3I Polytechnic service team were in the form of workshops with the theme of increasing understanding of Article 21 income tax calculations for students of SMK Ibnu Taimiyah Pekanbaru. Based on the information we got, there are still many people/taxpayers who do not understand how to calculate PPh 21 at least to calculate PPh 21 on their own income and from Ibn Taimiyah Vocational School students, the material they receive about PPh 21 at school is still not in detail, the discussion has not yet been reached. PPh 21 is owed to taxpayers, for that reason this socialization is carried out for SMK students majoring in Accounting which aims to make them understand the stages of calculating PPh 21. This socialization is about how to calculate PPh article 21 for taxpayers who are already working because the students of SMK Ibnu Taimiyah who majoring in Accounting does not rule out the possibility that upon graduating from school he immediately works in the Company as a financial staff or accounting staff who performs the calculation of Income Tax Article 21 for employees who work in the company or at least for the calculation of Income Tax Article 21 on the income he receives ( himself) . With this workshop, it was hoped that the participants will have knowledge, understanding and be able to calculate Income Tax Article 21 starting from the calculation of gross income, net income, non-taxable income and calculating income tax payable based on a predetermined tax rate.